Islam in South Asia : Revised, Enlarged and Updated Second Edition - Malik, Jamal, (Handbook of Oriental Studies. Section 2 South Asia ;, 2020)
Islam in South Asia: Revised, Enlarged and Updated Second Edition traces the roots and development of Muslim presence in South Asia. Trajectories of normative notions of state-building and the management of diversity are elaborated in four clusters, augmented by topical subjects in excursuses and annexes offering an array of Muslim voices. The enormous time span from 650 to 2019 provides for a comprehensive and plural canvas of the religious self-presentation of South Asian Muslims. Making use of the latest academic works and historical materials, including first-hand accounts ranging from official statements to poetry, Malik convincingly argues that these texts provide sufficient evidence to arrive at an interpretation of quite a different character. With major and substantial revisions, changes, abridgements and additions follow the academic literature produced during the last decades.